Concept of a human capital and its role in the economy and society - Azbergenova, R.B.; Knarbek, P.A. (BUKETOV BUSINESS REVIEW, 2017)
In modern conditions, human capital becomes the most important factor of economic growth and determines the future of the country. In the world practice, various indicators are used to assess the development of human capital, the most significant of which is the human development index or the human development index. The article reveals the concept of human capital, examines its essential characteristics, structure and features, analyzes various approaches to the classification of human capital types. The comparative analysis of the Human Development Index for 2015 for the countries of the world is given and the place of Kazakhstan is determined by the level of its development. It is noted that the relationship between human capital and the level of competitiveness of the national economy is directly proportional. The position of Kazakhstan in the rating of global competitiveness for 2015–2016 is analyzed. At this stage of development of our state, in order to improve the quality of human capital and, accordingly, to raise the level of competitiveness of the economy, it is necessary to change the role, first of all, of the education system, making it the centerpiece of a new model of economic growth. Under the conditions of economic modernization, the main tasks facing the state are the creation of a knowledge-based economy, raising the level of education and innovative potential of the country and radically transforming human capital.